Technology-Based Public Service Innovation in Infrastructure Development Management: A Study in South Sulawesi Province - Ilham Permana; Muhlis Madani; Ihyani Malik; Nuryanti Mustari (Lembaga Bale Literasi, 2026)
This study aims to comprehensively analyze technology-based public service innovation within the management of infrastructure development at the Department of Water Resources, Cipta Karya, and Spatial Planning of South Sulawesi Province. Employing a qualitative descriptive approach, empirical data were meticulously gathered through semi-structured in-depth interviews with key stakeholders, intensive field observations of digital dashboard operations, and extensive documentation analysis. The collected data were processed using the Miles and Huberman interactive model, encompassing data condensation, display, and conclusion drawing. The findings reveal that the implementation of the E-MONEV (Electronic Monitoring and Evaluation) system represents a paradigm shift from traditional bureaucratic reporting toward modern digital governance. Analyzed through the lens of Stephen P. Osborne’s Innovation in Governance framework, the innovation manifests across three critical dimensions: process innovation, public value, and public service governance. Process innovation is achieved through the integration of real-time tracking, GIS-based mapping, and automated reporting cycles that effectively eliminate manual bottlenecks. Public value is created through heightened transparency, where financial realization is strictly synchronized with physical progress, thereby fostering institutional accountability. Public service governance is reflected in the transition from hierarchical silos to collaborative digital networks involving external contractors and consultants. The study concludes that while E-MONEV has significantly modernized infrastructure supervision, its long-term success is contingent upon addressing the digital literacy gap and ensuring seamless technical integration across provincial systems.